Building New Tool for Software Project Planning Based on Meta-modeling Concepts and CMMI Meta-Standards - Husam Bofaoor (QALAAI ZANIST JOURNAL, 2021)
CMMI (Capability Maturity Model Integration) for development is a quality system targeting to improve the software development processes. It allows to measure organization maturity level and to improve its capacity in software development. MDE (Model Driven Engineering) is an approach that aims to automate the use of models in order to build more complex systems The software industry became a vital economic sector that employs a wide range of people. A quality assurance system becomes a real need to ensure the quality of software and to increase abilities of software companies to meet the requirements of customers. The paper aims to use a MDE approach to develop tools supporting any software company to adjust their software development process and then to meet the CMMI goals. this paper suggests a new structure of software development process in several models, and shows how to specify a metamodel for each step of this system. One of the advantages of the approach is very resilient and can support the software process development for several software companies and fit rapidly the changes in their software development process.